Effect of Mn-doping on optical properties of lead-free (K0.4Na0.6)NbO3 ferroelectric single crystals. Issue 8 (July 2020) - Hu, Yuqing; Xie, Qingxiu; Wu, Yang; Zhao, Xiangyong; Tang, Yanxue; Wang, Feifei; Duan, Zhihua; Lin, Di; Luo, Haosu; Liang, Ruihong
Abstract: Optical properties of <001>-oriented pure (K0.4 Na0.6 )NbO3 (KNN) and 0.5 wt% Mn-doped KNN (Mn-KNN) single crystals were studied. The refractive indices ( n ) of both crystals exhibited a normal dispersion behavior in the wavelength range of 300−1100 nm. The modified Sellmeier dispersion equations for n were obtained by least-squares fit. In addition, Sellmeier coefficients were determined by single-oscillator dispersion relation, which related to energy band structures of crystals. Compared with KNN, a decrease about 10 % in transmittance (over 350 nm) was observed in Mn-KNN due to the losses resulting from the increase of domain wall density. Furthermore, a 20 nm blue-shift in the absorption edge was observed for Mn-KNN. Based on Tauc equation, the band gap energies of 3.26 and 3.42 eV were obtained for KNN and Mn-KNN, respectively. The increase of band gap energy in Mn-KNN was attributed to the distortion of BO6 octahedron building block caused by Mn 2+ occupying the B-site.